Improving Social Studies Learning Outcomes Through the Make A Match Learning Model for Class VI Students at SD Inpres Bontoloe, Gowa Regency - Supardi Salam (International Journal of Education, Vocational and Social Science, 2023)
This research is an effort to improve social studies learning outcomes through the application of the make a match type cooperative learning model. The formulation of the problem in this research is how to improve social studies learning outcomes through the make a match type cooperative learning model for Class VI students at SD Inpres Bontoloe, Gowa Regency? The aim of this research is to determine social studies learning outcomes through the make a match learning model for Class VI students at SD Inpres Bontoloe, Gowa Regency. The approach used is descriptive qualitative and the type of research used is classroom action research. The research focus is process and results. The research subjects were 21 students in Class VI of SD Inpres Bontoloe, Gowa Regency, consisting of 11 girls and 10 boys, plus 1 teacher. Data collection using observation and test techniques. The data was analyzed descriptively qualitatively by describing the learning process for each cycle. The research results showed that there was an increase in learning outcomes from cycle I to cycle II through the application of the make a match learning model. In cycle I it was in the fairly good category because the teacher had not implemented the learning steps through implementing the make a match learning model well, while the learning results in cycle II were in the good category. The conclusion of this research is that the application of make a match can improve social studies learning outcomes for Class VI students at SD Inpres Bontoloe, Gowa Regency.